The intellectual and cultural contributions of Raja Ali Haji (1809-1870) in nineteenth-century Malay thought and literature - Muhammad Aiman Rahim (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
This study examines the literary and intellectual contributions of Raja Ali Haji to the Malay world. It begins by discussing the intellectual history of the Malay world prior to the time of Raja Ali Haji. This discussion provides background information on the intellectual development in the Malay world leading to the time of Raja Ali Haji. It shows how Malay scholars in the 17th century such as Nuruddin ar-Raniri, Syeikh Hamzah al-Fansuri, Syeikh Shamsuddin -Sumatrani and others contributed to various disciplines such as history, theology and Sufism. This study then provides an overview of Raja Ali Haji's literary and philosophical works such as Thammaratul Muhimmah, Tuhfat an-Nafis, Bustanul Katibin Li Sibyan and others. The third chapter is the heart of this research as it discusses the political thought of Raja Ali Haji based on his work Thammaratul Muhimmah. This book tells its readers on how to build an Islamic government according to the principles of Islam and gives examples from past Islamic civilisations. Finally, this study examines the reception to the works of Raja Ali Haji by foreign and local scholars who lived during his time and after his death. It also compares the contributions of Raja Ali Haji with those of two other prolific Malay scholars who lived after him, namely, Hamka and Za'ba. The primary sources used in this research are mainly the writings of Raja Ali Haji himself such as Tuhfat an--AlNafis, Gurindam 12, Bustanul Katibin, Thammaratul Muhimmah, Syair Hukum Nikah and others.